Antioxidant and Antipathogen Activities of Fermented Juice and Crude Extract of Tinospora crispa (L.) Hook f. & Thomson - Nilsang, Poonyanuch (YRU Journal of Science and Technology, 2021)
In present, herbal fermented juice are widely sold as community products but there are still few academic contributions. The objective of this research was to assess the antioxidant and anti-pathogenic activities of Tinospora crispa (L.) Hook f. & Thomson fermented juice, which continuously fermented for 12 weeks compared with its crude extract using ethanol as a solvent. Antioxidant activities were evaluated by % DPPH radical scavenging and the anti-pathogen activity against 7 stains including; Escherichia coli TISTR073, Escherichia coli TISTR780, Pseudomonas aeruginosa TISTR781, Staphylococcus aureus TISTR1466, Staphylococcus aureus TISTR2329, Staphylococcus epidermidis TISTR518 and Candida albicans TISTR5554. The results revealed that the Tinospora crispa crude extract showed higher antioxidant than its fermented juice. The antioxidant activity of the T. crispa crude extract and the fermented juices were 85.10 and 49.43 %DPPH radical scavenging, respectively. The results of the anti-pathogen activity also showed that T. crispa crude extracts can inhibit all stain of test microorganisms but did not effective in killing P. aeruginosa TISTR781 and C. albicans TISTR5554. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC) were 3.64-29.15 and 58.3-233.2 mg per milliliter, respectively. While, T. crispa fermented juices had an efficiency in inhibiting microorganisms after two weeks of fermentation. It could inhibit growth of E. coli TISTR073, E. coli TISTR780, P. aeruginosa TISTR781, S. aureus TISTR1466, S. aureus TISTR2329, S. epidermidis TISTR518, but did not inhibit growth of C. albicans TISTR5554. The MIC of the fermented juice was 6.25-100 % (v/v). And it was also found that T. crispa fermented juices were ineffective in killing all types of studied microorganisms.